Every inch a king
1 online resource (xvi, 411 pages)
Keywords: The role of kings, the source of their authority and the nature of the practical restraints on their power have exercised political and religious philosophers, historians, competing candidates for rule and subject populations from the time of the earliest documented human societies. How the kingly image is created and presented and how the ruler performs his or her function as the source of justice are among the topics addressed in this volume, which also covers the role of queens in maintaining dynastic succession yet being the target of tales of adultery. This volume is of particular interest in bringing together studies of kingly power from Cyrus the Great and Alexander in the ancient world to Shah Abbas in the seventeenth century, and covering the European Middle Ages as well as Iran and the Muslim world.